Kenya - Giles, Bridget, 1970- (Washington, D.C. : National Geographic, 2006)
"Discover the people and places of Kenya."--Source other than the Library of Congress.
Foreword -- Geography -- What's the weather like?: Average temperature & rainfall -- Fast facts -- Physical map -- Special feature: Sacred mountain -- Special feature map: Rifting through Kenya -- Nature -- Wealth of wildlife -- Diverse ecosystems: Species at risk -- Vegetation & ecosystems map -- Special feature map: Masai -- Mara migration -- Special feature: Maneless man-eaters -- Special feature: Wangari maathai -- History -- All human history -- First herders and farmers: Time line -- Historical map -- Special feature map: Fossils and their finders -- Special feature map: Trading -- Network -- Special feature map: Dedans Kimathi -- People & culture -- Many cultures and tongues -- Rural and urban population: Common Swahili phrases -- Population map -- Special feature: Street talk -- Special feature: National -- Holidays and festivals -- Government & economy -- New nation -- Provinces and president: Trading partners -- Political map -- Special feature: Jomo -- Kenyatta -- Special feature: How the government works -- Special feature map: Agriculture -- Glossary -- Special feature: Writing a report -- Bibliography -- Index -- Credits.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Map on lining paper.
Includes bibliographical references (p. 61) and index.
Description based on print version record.
Keywords: Kenya -- Juvenile literature; Kenya; Electronic books- OSLIS; Electronic books